Bioeletrodo para detecção da amilase salivar humana - Santos, Tatiane Vanessa da Silva (2010)
The salivary alpha-amylase is one of the most abundant protein in saliva and several studies evaluate differences in activity and concentration of HSA in order to use it as a potential biomarker for diagnosis of some diseases. This paper describes the preparation and purification of human salivary alpha-amylase and anti-alpha-amylase polyclonal antibody, as well as its utilization in the development of a novel bioelectrode based on the immobilization of a specific antibody for salivary amylase onto graphite electrode modified with poly(3- hydroxyphenylacetic) acid. The bioelectrode was incubated with salivary amylase or lysozyme (interfering salivary) and the interaction between the antibody and the enzymes was analyzed through electrochemical impedance spectroscopy. The results indicated specificity of the bioelectrode of salivary amylase. The method used is rapid, easy to use, label-free and inexpensive.